Symbolic struggles over solidarity in times of crisis: trade unions, civil society actors and the political far right in Austria. Issue 5 (20th October 2019) - Hofmann, Julia; Altreiter, Carina; Flecker, Jörg; Schindler, Saskja; Simsa, Ruth
ABSTRACT: As a consequence of the recent financial and economic crisis, social cohesion and integration are in jeopardy all over Europe. In this context, scholars also speak of decreasing solidarity, which is defined as a normative obligation to help each other and to make sacrifices to reach common goals. By taking the empirical example of Austria, we argue that the meaning of solidarity is increasingly being contested. Various collective actors such as trade unions, civil society actors, but also right-wing populist parties are engaged in symbolic struggles over solidarity. To show this, we examine the different concepts and foundations of solidarity and analyse where and why they conflict with each other, referring to recent debates on political issues, such as the needs-based minimum benefit system and the access to the labour market for refugees.